QUANTITATIVE GENETIC ANALYSIS OF PHENOLIC ACIDS IN OILSEED RAPE MEAL - Florin-Daniel LIPȘA; Rod SNOWDON; Benjamin WITTKOP; Wolfgang FRIEDT (Journal of Applied Life Sciences and Environment, 2023)
Rapeseed meal, a by-product of oilseed extraction related to the agri-food and biofuel industries due to its favourable composition of essential amino acids, is currently utilised for animal feed. In this study, 166 doubled haploid (DH) rapeseed lines from the segregating Brassica napus doubled haploid population YE2-DH were genetically and chemically analysed for phenolic acids. The relationship between seed colour and phenolic acid fractions in B. napuswas investigated using these analyses to improve the quality of rapeseed meal. High-performance liquid chromatography assays were used to estimate phenolic acid content, and the outcomes were used to identify quantitative trait loci (QTL). Nine quantitative feature loci for three distinct phenolic acid compounds were mapped to seven linkage groups. A minor QTL for sinapine was located on linkage group C05 in the same interval as the QTL for seed colour. On chromosome A09, two loci for phenolic acids colocalised with the main QTL for seed colour. Closely linked molecular markers for the target traits (seed colour, phenolic acids) identified during this study could be useful tools for breeding new oilseed rape cultivars with lower levels of antinutritive compounds.